Profile of parotid tumors visiting tertiary health care facility in North India - Munjal, Manish; Tuli, Nitika; Rishi, Porshia; Singh, Harjinder; Talwar, Shivam; Sharma, Salony; Munjal, Shubham (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Neoplastic lesions of head and neck presenting in a tertiary care facility were analyzed. This study is proposed to examine the epidemiological pattern of parotid tumors, histopathology correlations and relation of facial nerve with the parotid tumors. Methods: This is a retrospective study of patients with head and neck neoplasms who presented to the ENT tumour clinic of Dayanand Medical College and Hospital over a period of 2 years i.e., from January 2018 to December 2019. Patients’ demographic profile, histopathological reports and pre-operative fine needle aspiration cytology reports were studied. Results: Total number of cases of head and neck neoplasms were 273 over a period of 2 years. Parotid tumours constituted 9.1% of the total head and neck neoplasm. Predominant age group in case of benign parotid tumors was 40-50 years, whereas in case of malignant neoplasms was 50-60 years. Posterior belly of digastric along with tragal pointer are the most consistent and reliable landmarks for Identification of facial nerve. Conclusions: Identification of trunk of facial nerve using anatomical landmarks is the keystone for parotid surgery. Posterior belly of digastric along with tragal pointer are the most consistent and reliable landmarks for Identification of facial nerve.